2021
DOI: 10.1371/journal.pone.0248665
|View full text |Cite
|
Sign up to set email alerts
|

Identification and predictability of soil quality indicators from conventional soil and vegetation classifications

Abstract: The physical, chemical and biological attributes of a soil combined with abiotic factors (e.g. climate and topography) drive pedogenesis and some of these attributes have been used as proxies to soil quality. Thus, we investigated: (1) whether appropriate soil quality indicators (SQIs) could be identified in soils of Great Britain, (2) whether conventional soil classification or aggregate vegetation classes (AVCs) could predict SQIs and (3) to what extent do soil types and/ or AVCs act as major regulators of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ferralsols, Acrisols, Nitosols, Anthrosols, and Greyzems exhibited significantly lower SQI values than the other soil types ( p < 0.05). SQ is measured by comprising soil indicators, the influence of soil types on SQ was therefore inferred from its indicators (Simfukwe et al, 2021). The one‐way ANOVA results showed that the scores of silt, TP, TK, Ca++, and vermiculite were generally lower of these five soil types than of other soil types (Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…Ferralsols, Acrisols, Nitosols, Anthrosols, and Greyzems exhibited significantly lower SQI values than the other soil types ( p < 0.05). SQ is measured by comprising soil indicators, the influence of soil types on SQ was therefore inferred from its indicators (Simfukwe et al, 2021). The one‐way ANOVA results showed that the scores of silt, TP, TK, Ca++, and vermiculite were generally lower of these five soil types than of other soil types (Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…Since micro-organisms could act directly or indirectly on organic matter decomposition and the promotion and maintenance of several soil properties, some characteristics of soil microbial communities have been used as ecological indicators of ecosystem disturbances and plant cover restoration (Gama-Rodrigues et al, 2008 ; Muñoz-Rojas et al, 2016 ); e.g., the microbial biomass is considered one of the most sensitive and effective indicators because it is directly influenced by biotic and abiotic factors (Karlen et al, 2019 ; Nunes et al, 2020 ). Soil microbial and biochemical properties, such as the metabolic quotient (qCO 2 ) (ratio basal respiration: microbial carbon C) and microbial quotient (qMIC) (ratio microbial C: organic C), are also cited in the literature as efficient properties to evaluate the soil health (Maini et al, 2020 ; Simfukwe et al, 2021 ). On the other hand, soil biochemical properties are already established indicators of soil health, but there is still no consensus as to how they should be used.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy soil is a key for sustaining the health of plants and the environment . The microbial community (also known as the microbiome) is one of the dominant factors in soil health, in addition to the soil organic matter, soluble and reduced nitrogen, soil topography, water holding capacity, and climate . Therefore, any perturbation in the microbiome population can lead to serious health effects on plants and the environment .…”
Section: Introductionmentioning
confidence: 99%